Evaluasi Knowledge Management System di Kompas Gramedia Menggunakan Analisis Faktor - Desi Maya Kristin; Wahyu Sardjono (Bina Nusantara University, 2013)
Evaluation of Knowledge Management System (KMS) is performed to determine the state of KM Portal and provide suggestions to improve the benefits and usability for employee and the company. The evaluation analysis of KMS uses factor analysis to determine the factors that influence user awareness in using KM Portal of Kompas Gramedia. The analysis shows three factors: the quality of KM Portal and user support; user participation; processes and procedures. All factors produced a model that can be used for the control of KM Portal. In accordance with the data processing, the current state of KM Portal is enough. This situation has not yet met the standards that company desires so the company needs further development to obtain a perfect score.